PERENCANAAN PEMBANGUNAN DI INDONESIA PASCAORDE BARU: REFLEKSI TENTANG PENGUATAN PARTISIPASI MASYARAKAT - Helmy Fuady (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2012)
The development planning during the New Order period has been criticized becauseit was centralistic, technocratic and lack of public participation. In the reformationera, many important changes have influenced the development planning system inIndonesia. The changes include changing role of the Bappenas (National DevelopmentPlanning Agency), decentralization, direct presidential and local head elections, aswell as the strengthening roles of the parliament. This paper analyses whether ornot these changes open a wider space for public participation in the developmentpolicy-making. The discussion shows that public participation has not yet as expectedby theory. The mechanism for public participation inthe development planning did notchangemuch compared to the situation during the New Order era. Public participationhas only fairly achieved and political elites are dominating the policy-making arena.Keywords: development planning, democracy, participation.